Social inequalities in the characterization of HIV/Aids cases in Alagoas - Amorim, Victória Khrystty Calheiros de; Marques, Carla Cláudia Guilherme da Silva; Freitas, Rosa Caroline Mata Verçosa de (JRG Journal of Academic Studies, 2023)
HIV/AIDS is a serious public health problem in Brazil, especially in regions of high social vulnerability, such as the Northeast. In this context, social inequalities are determining factors in the characterization of these cases. General objective: To analyze the social inequalities in health in the characterization of HIV/AIDS cases in the state. Method: This is an epidemiological, descriptive, retrospective study of quantitative and socioeconomic approach of HIV/AIDS cases in the state of Alagoas in the period between 2010 and 2021. Results and Discussion: According to the data gathered, 5,566 cases of HIV/AIDS were reported in the Notifiable Diseases Information System. Conclusion: The epidemiological profile of HIV/AIDS cases in the state of Alagoas between 2010 and 2022 are of young people between 15 and 25 years old, male, brown, with incomplete elementary education and heterosexual.